The effectiveness of a dose based reporting tool in reducing vaccine wastage at primary care clinics in Delhi, India: an operational research study - Ruchir Rustagi; Saurav Basu; Pragya Sharma; Nandini Sharma (Taylor & Francis Group, 2021)
Minimizing vaccine wastage and associated costs is considered a key target for appropriate vaccine management. In India, the Rotavirus Vaccine (RVV) (2019) and the fractionated injectable polio vaccine (f-IPV) (2016) are more prone to wastage with high procurement costs. In this operational research study, we determined the effectiveness of a (self-designed) dose based reporting tool (DBRT) in reducing vaccine (f-IPV and RVV) wastage at primary care facilities in India during December 2019 to March' 2020. Data reports of all the immunization sessions conducted at three primary care facilities were analyzed to calculate the wastage rates of the RVV and the f-IPV for the following periods: (1). Period of initiation (August-November' 2019) (2). Pre-intervention with sensitization of healthcare providers (December' 2019-January' 2020) (3). Post-intervention after application of the DBRT. Intervention: The DBRT is a paper-based reporting format that assigns a unique code to each RVV and IPV vial. The health facility is required to report the total doses administered from each coded vial during every immunization session by updating it on the assigned reporting format. Pre-intervention, the average monthly wastage of f-IPV was 23.5% and of the RVV ranged from 18%-31%. Post-intervention, on using the DBRT, the monthly wastage of both RVV and f-IPV dropped significantly to 8.6% and 11.4%, respectively. During the subsequent month, the IPV wastage further decreased to only 4.7%. In conclusion, the DBRT reduces vaccine wastage in government primary care facilities by enabling a paper audit trail that promotes responsiveness and accountability among healthcare workers directly involved in vaccine administration.